THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITY, AND LEVERAGE ON TAX AGGRESSIVENESS - Trismayarni Elen; Dwi Prihatini; Selfiani; Yulia Mugi Utami (ZILLZELL MEDIA PRIMA, 2024)
In that fact, have been found many cases that companies try to reduce their tax payment obligations through various means, for example not including actual sales volumes in financial report, high corporate social responsibility disclosure, corporate debt, and so forth. This study aims to analyze the effect of corporate social responsibility, profitability and leverage on tax aggressiveness. The type of data used is secondary data. The sample selection used isa purposive sampling method from the annual report on the official Indonesia Stock Exchange (IDX) website and obtained 26 manufacturing companies in the food and beverage sub-sector with certain criteria in 2018-2021. The techniques of hypothesis testing use multiple regression analysis. The results showed that corporate social responsibility, profitability, and leverage had a positive effect and significant on tax aggressiveness.